Dynamic Nonmyopic Portfolio Behavior - Kim, Tong Suk; Omberg, Edward (Review of Financial Studies, 1996)
[The dynamic nonmyopic portfolio behavior of an investor who trades a risk-free and risky asset is derived for all HARA utility functions and a stochastic risk premium. Conditions are found for when the investor holds more or less than the myopic amount of the risky asset; hedges against or speculates the risk-premium uncertainty; is long or short on the risky asset; and holds more or less of the risky asset at longer horizons. The analytical solutions derived take multiple mathematical forms and include extreme cases in which investors with long but finite horizons can attain nirvana.]